2016
DOI: 10.1371/journal.pone.0152673
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Genetic Heterogeneity Delineated by Multi-Region Sequencing

Abstract: Intratumor heterogeneity (ITH) leads to an underestimation of the mutational landscape portrayed by a single needle biopsy and consequently affects treatment precision. The extent of colorectal cancer (CRC) genetic ITH is not well understood in Chinese patients. Thus, we conducted deep sequencing by using the OncoGxOne™ Plus panel, targeting 333 cancer-specific genes in multi-region biopsies of primary and liver metastatic tumors from three Chinese CRC patients. We determined that the extent of ITH varied amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…We obtained: (a) a clonal group of 34 mutations detected in all samples (b) a subclonal group of 3 mutations private to the metastatic regions, and (c) 8 mutations with distinct mutational profiles. The clonal group contains mutations in key colorectal driver genes such as APC, KRAS, PIK3CA and TP53 [15], Edmonds's model predicts branching evolution and high levels of ITH among the subclonal populations, consistently with the original phylogenetic analysis by Lu et al [40] ( Figure 5B). In particular, the subclonal trajectory that characterizes the primary regions is initiated by a stopgain SNV in the DNA damage repair gene ATM, whereas the subclonal metastatic expansion seems to originate by a stopgain SNV in GNAQ, a gene reponsible for diffusion in many tumour types [41].…”
Section: Analysis Of Patient-derived Multi-region Data For a Msi-highsupporting
confidence: 77%
See 1 more Smart Citation
“…We obtained: (a) a clonal group of 34 mutations detected in all samples (b) a subclonal group of 3 mutations private to the metastatic regions, and (c) 8 mutations with distinct mutational profiles. The clonal group contains mutations in key colorectal driver genes such as APC, KRAS, PIK3CA and TP53 [15], Edmonds's model predicts branching evolution and high levels of ITH among the subclonal populations, consistently with the original phylogenetic analysis by Lu et al [40] ( Figure 5B). In particular, the subclonal trajectory that characterizes the primary regions is initiated by a stopgain SNV in the DNA damage repair gene ATM, whereas the subclonal metastatic expansion seems to originate by a stopgain SNV in GNAQ, a gene reponsible for diffusion in many tumour types [41].…”
Section: Analysis Of Patient-derived Multi-region Data For a Msi-highsupporting
confidence: 77%
“…Multi-region P3 ( Figure 5: A. Multi-region sequencing data for a MSI-high colorectal cancer from [40], with three regions of the primary cancer: p3-1, p3-2 and p3-3, and two of one metastasis: L-1 and L-2.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…ITH complicates biomarkers discovery and therapeutic intervention given to the patient. Previous genomic studies have shown that biopsy from a single tumor and multiple tumors failed to give a comprehensive picture of a tumor's genomic mutational landscape . This holds true for proteomics analysis as well where single regional biopsy or a small chunk of a tumor may underestimate the proteome landscape of heterogeneous tumors.…”
Section: Implications Of Proteome Heterogeneity In Biomarker Discovermentioning
confidence: 99%
“…CRC tumor heterogeneity has been reported at the genetic and protein levels . Numerous researches based on genomic and transcriptomic profiles have been done to reveal the extensive intertumor heterogeneity in CRC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation